ANALYSIS OF SIYASAH DUSTURIAH ON THE FORMATION OF NAGARI REGULATIONS: A STUDY IN NAGARI PAGARUYUNG - Dola Dinia Putri; Dian Pertiwi; Alfi Husni (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
The main problem in this article is the authority of the Wali Nagari in establishing Nagari Regulations in Nagari Pagaruyung based on Tanah Datar Regent Regulation Number 10 of 2021 concerning Technical Guidelines for Nagari Regulations and the inhibiting factors for the Wali Nagari in carrying out the function of establishing Nagari Regulations in Nagari Pagaruyung. The aim of this research is to explain, analyze, and determine the authority of the Nagari Wali in establishing Nagari Regulations as well as the factors inhibiting the Wali Nagari in carrying out the function of establishing regulations in Nagari Pagaruyung. The type of research that the author uses is empirical juridical research, which was carried out in Nagari Pagaruyung. From the research conducted by the author, it can be concluded that the Nagari Pagaruyung Government has not fully implemented the articles explaining the mechanism for forming Nagari Regulations and lacks coordination with the authorized institutions in forming Nagari Regulations. Additionally, the efficiency of the time used and the low level of apparatus resources are also issues. The Nagari Government's understanding of the mechanism for establishing Nagari Regulations, and the absence of experts or researchers who can provide education, is an inhibiting factor for the Nagari Guardians in carrying out their function in establishing regulations in Nagari Pagaruyung.